Segmented labor markets and unemployment - Assar Lindbeck; Dennis J. Snower (Institute for International Economic Studies, University of Stockholm; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
This paper suggests various alternatives to the Harris-Todaro theory in explaining unemployment in segmented labor markets. We focus on a labor market with i perfectly competitive secondary sector and an imperfectly competitive primary sector, the latter combining salient features of the efficiency wage, insider-outsider, and bargaining theories of employment and wage formation. Unemployment and labor market segmentation are explained with reference to heterogeneous preferences, productivities, and endowments among workers. The responsiveness of unemployment to external shocks is shown to depend crucially on whether the above heterogeneities are exogenously given or whether they are endogenously generated through workers' employment histories.
Keywords: 330